The Effect of Problem Based Learning on Students' Mathematical Problem-Solving Skills and Self-Efficacy - Wahyu Sianipar; Dhoriva Urwatul Wutsqa; Imam Nursahid (Universitas Teknokrat Indonesia, 2026)
This study aims to determine the effect of the Problem Based learning model on mathematical problem-solving ability and self-efficacy of eighth-grade junior high school students in statistics material. Problem based learning is an innovative learning model that emphasizes the active involvement of students in the contextual problem-solving process, so it is believed to be able to encourage the development of critical thinking skills and increase students' self-confidence in their learning process and outcomes. This study used a quantitative approach with a one-group pretest-posttest pre-experimental design. The subjects in this study were 32 students of class VIII-G SMP Negeri 8 Yogyakarta who were selected through a purposive sampling technique. The research instrument consisted of a descriptive test to measure problem-solving ability and a Likert scale questionnaire to measure students' self-efficacy. The data obtained were analyzed descriptively and inferentially with a paired sample t-test. The results showed that there was an increase in the average score of problem-solving ability from 61.41 in the pretest to 81.84 in the posttest. Similarly, students' self-efficacy scores increased from an average of 45.41 to 71.22 after treatment. Statistical tests showed that the difference in scores was statistically significant (p < 0.001). These results indicate that the implementation of the Problem-Based Learning model significantly positively impacted students' problem-solving abilities and self-efficacy. Therefore, the PBL model can be used as a strategic alternative in mathematics learning to foster higher-order thinking skills and build self-confidence in completing academic tasks.